1992
DOI: 10.1088/0268-1242/7/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave attenuation by localized electrons in a 2DEG at a GaAs/AlGaAs heterojunction

Abstract: The surface acoustic wave (SAW) transmission has been measured at 4.2 K, as a function of magnetic field up to 5 T. for a GaAs wafer on which a heterojunction has been grown by MBE. Frequencies up to 1920 MHz were generated by interdigital SAW transducers deposited directly on the GaAs surface At all frequencies, oscillations in the SAW attenuation, analogous to the Shubnikov-de Haas oscillations in o x x , can be observed due to piezoelectric coupling to the non-localized electrons of the two-dimensional ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
1
13
1
Order By: Relevance
“…However, this method is inconvenient because it is almost impossible to determine the width of the gap by direct measurements. In experiments employing the second configuration there is no gap at all, but in this case the deformation interaction of the 2D electrons with the SAWs cannot be ignored [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method is inconvenient because it is almost impossible to determine the width of the gap by direct measurements. In experiments employing the second configuration there is no gap at all, but in this case the deformation interaction of the 2D electrons with the SAWs cannot be ignored [6].…”
Section: Introductionmentioning
confidence: 99%
“…The first configuration was used in [4] and the second was used in [5][6][7][8]. In all of these investigations it was concluded that the character of the dependence of the SAW absorption coefficient of the two-dimensional electrons on the magnetic field H is determined by the dc conductivity σ dc xx (H) and its dependence on H. However, in [9], where the SAW absorption of a 2DEG in a InGaAs/InP heterostructure was measured in the first experimental configuration with T =4.2 K, it was shown that this assertion is valid only for high Landau-level numbers and in stronger magnetic fields (i.e., small filling numbers ν = nhc/2eH, where n is the Hall electron density) the variation of the SAW absorption coefficient as a function of H is not determined by σ dc xx (H).…”
Section: Introductionmentioning
confidence: 99%
“…As has been pointed out before, SAW absorption measurements are particularly sensitive at very low conductivities, a fact that has been used before to study the dynamical conductivity of quasi-twodimensional electron systems ͑Q2DES͒ in the regime of the quantum Hall effect. [6][7][8] The design of our sample is shown in Fig. 1.…”
mentioning
confidence: 99%
“…The interaction between surface acoustic waves ͑SAWs͒ and high-mobility quasi-two-dimensional electron systems ͑2DES͒ has recently attracted much attention. [1][2][3] SAWs proved to be a powerful tool for the investigation of the dynamical conductivity of such systems as they represent a highly sensitive dynamical probe which averages over the whole 2DES. SAW techniques have in the recent past been successfully applied to investigate the properties of a 2DES in the regimes of both the integer and the fractional quantum Hall effect at low temperatures and in high magnetic fields.…”
mentioning
confidence: 99%